Hubungan antara Gerakan Repetitif dan Lama Kerja dengan Gejala Carpal Tunnel Syndrome pada Pekerja Sektor Informal Pengelola Hasil Laut - Rosiyana, Rosiyana; Koesyanto, Herry (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Carpal Tunnel Syndrome (CTS) is occupational diseases caused by repetitive movements that are carried out monotonously and continuously for a long time. Repetitive movements that are carried out for a long time can cause the median nerve at the wrist to be pinched or compressed. The purpose of this study was to determine the relationship between repetitive movements and duration of action with symptoms of carpal tunnel syndrome.Methodes: This type of research is quantitative research using cross sectional method and using total sampling in which the entire population is used as a research sample with a total of 62 samples. The instruments used are data questionnaires, Data analysis was carried out using Chi Square test with SPSS version 22.0.Results: The data from this study indicate that there is a relationship between repetitive movements and symptoms of CTS (p = 0.000). This study also showed that there was a relationship between length of work and symptoms of CTS (p = 0.001).Conclusion: The conclusion is that there is a relationship between repetitive movements and length of work with symptoms of carpal tunnel syndrome in informal sector workers managing marine products (fish, crab and shellfish) in the Citemu Trade Business.